Effects of salinity levels in Oryza sativa in different phenological stages under greenhouse conditions - Cobos Mora, Fernando; Gómez Pando, Luz; Reyes Borja, Walter; Hasang Moran, Edwin; Ruilova Cueva, María; Duran-Canare, Perry Lorraine (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
In this research, the agronomic and yield components of rice were evaluated, subjected to different levels of salinity at different phenological stages. It was made on the greenhouse of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, Ecuador. It was established an internally casualized delineation with an 8 X 3 factorial start with four repetitions, corresponding to only phenological phases of growth in three doses of salinity (dS.m-1). According to the results obtained, it is concluded that some agronomic characteristics are affected by high levels of salinity (7.0 dS.m-1), showing significant differences less than 0.05 between the treatments, as in the case of vigor whose level was 7.0 dS. m-1. In the same way, chlorophyll levels are significantly reduced between treatments, being a level of 7.0 dS.m-1 or more severe. It is evident that high levels of salinity are detrimental to yield variations, once at 7.0 dS.m-1, or weight of 1000 grains decreased by 54 %, in quantity or panicle compression by 68 %. Furthermore, it affects other phenophases such as flowering, development and pickling of its vegetative cycle, mainly in the phases of germination, molting, profile and growth of caule.